'A2 is Normal' – Thai Secondary School English Teachers' Encounters with the CEFR. (December 2018) - Franz, Jens; Teo, Adisa
Thailand has seen several English language curriculum reforms over the last 20 years, all of which were found to have failed to lift Thai students' standard of English language proficiency across all levels of study. In 2014, the Thai Ministry of Education announced the introduction of the Common European Framework of Reference for Languages (CEFR), in combination with Communicative Language Teaching (CLT), as its latest policy to improve the standard of English learning and teaching in Thailand's schools. The establishment of the ASEAN Economic Community (AEC) in 2015 and concerns about the economic competitiveness of the Thai labour force were provided as the underlying rationale for this policy change. This case study, using Grounded Theory Methodology combining semi-structured in-depth interviews, a questionnaire and document analysis, addresses the question of how this education policy change was experienced and perceived by English language teachers at state secondary schools across four provinces in the south of Thailand. A marked divergence in individual teachers' knowledge and appreciation of the policy plans was observed, with the majority of respondents displaying indifference to and ignorance of the policy. The Ministry had in 2015 tested all civil servant English teachers in a CEFR-referenced online placement test, where 94% had failed to reach the targeted proficiency level of B2. Consequently, the framework was perceived primarily as an English proficiency test for teachers, a European assessment scale which had been applied to them, but which had had no further application to either classroom teaching or student assessment. These findings are framed in the wider context of curriculum reform and English language teaching in Thailand. Comparisons with other English curriculum reform policies based on the CEFR are made, and the emphasis on testing teachers' language proficiency is reflected upon through the wider debate on language teacher proficiency.